The Impact of Talent Management and Cyberloafing on Employee Performance: The Mediating Role of Job Satisfaction - Ria Estiana; Ari Susanti; Susbiyantoro; Himawan Pramulanto; Niantoro Sutrisno (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The goal of this research is to explore how talent management and cyberloafing behavior affect employee performance, with job satisfaction acting as a mediating factor. The study focuses on the increasing occurrence of cyberloafing in digital workplaces and highlights the significance of talent management strategies in improving employee productivity. A quantitative method utilizing structural equation modeling-partial least squares was used to examine the connections between talent management, cyberloafing behavior, job satisfaction, and employee performance. The study sample included permanent employees from LP3I College in the West Java region, chosen through purposive sampling. The findings indicate that talent management has a significant effect on both job satisfaction and employee performance. Conversely, cyberloafing behavior negatively impacts performance but does so indirectly through job satisfaction. Job satisfaction was identified as a significant mediator, strengthening the relationship between talent management and performance while mitigating the significant impact of cyberloafing. The study concludes that organizations should prioritize enhancing talent management practices and creating a work environment that fosters job satisfaction. These measures can help minimize the negative impact of cyberloafing and encourage overall improvements in employee performance.